Perbedaan Gender dalam Peran Konflik, Emosional Kerja, dan Kinerja Pegawai Marketing Perusahaan Farmasi di Jawa Tengah - Naning Kristiyana (Jurnal Maksipreneur, 2018)
Marketing employees as the heart of the company have a duty to achieve good performance, work targets must be fulfilled in an effort to contribute to the company's performance. Gender differences in the domestic role of families with work and emotional differences in gender can provide benefits in the recruitment process and the job description of marketing employees. This study aims to determine differences between female employees and male employees in the role of work conflict and to know the differences between female employees and male employees in emotional work and performance as marketing employees of pharmaceutical companies. The sample of all marketing staffs of Takeda Indonesia Pharmaceutical Company in Central Java is 16 people. Primary data collection was done by a questionnaire. This research uses a quantitative descriptive method. The analysis of data uses an ANOVA analysis. The analysis of variance (ANOVA) is used because there are two independent variables with combinations scales, namely interval and nominal (gender), while the dependent variable is interval scale. The results of this research showed that the roles of conflict and performance have no differences between male employees and female employees. For emotional intelligence, there are differences between male employees and female employees. The significant differences mean that there are a real differences between male employees and female employees in their emotional intelligence. Self-control and self-motivation as a form of emotional intelligence showed differences between male marketing employees and female marketing employees.